2019
DOI: 10.1080/02813432.2019.1619829
|View full text |Cite
|
Sign up to set email alerts
|

The when and how of the gynaecological examination: a survey among Norwegian general practitioners

Abstract: Introduction: Little is known about the indications general practitioners (GPs) perceive as relevant for performing gynaecological examinations (GEs), how GPs master the GE and associated procedures, and how they handle the sensitive nature of GEs. Methods: In 2015, 70 medical students at the University of Bergen distributed a questionnaire to all 175 GPs in the practices they visited. The questions covered practical routines related to GEs, insertion of intrauterine device, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In a multi-country European study with 366 participants, male trainees in various specialties felt more confident than female trainees in dealing with patients with sexual dysfunctions [ 17 ]. In addition, a recent Norwegian study with 152 GPs showed that male GPs were more reluctant to perform gynecological examinations on their patients compared to female GPs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-country European study with 366 participants, male trainees in various specialties felt more confident than female trainees in dealing with patients with sexual dysfunctions [ 17 ]. In addition, a recent Norwegian study with 152 GPs showed that male GPs were more reluctant to perform gynecological examinations on their patients compared to female GPs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One cultural issue to note in these cases is the reluctance among all levels of medical personnel to perform a manual vaginal examination 8 . Instead of performing a simple, manual exploration to determine if packing material is present in the vagina, health care providers often rely on perfunctory perineal observation or expensive radiographic studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 One cultural issue to note in these cases is the reluctance among all levels of medical personnel to perform a manual vaginal examination. 8 Instead of performing a simple, manual exploration to determine if packing material is present in the vagina, health care providers often rely on perfunctory perineal observation or expensive radiographic studies. Although manual vaginal examinations are not taught in nursing schools, training is provided for nurses on labor and delivery and gynecology units and can serve as a resource for nurses on other units.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian study, three-quarters of women preferred to see a female practitioner for a Pap smear [ 22 ]. A Norwegian study found that male GPs more often omit performing a gynaecological examination [ 23 ]. Insecurity regarding cervical screening due to little practice might be a contributing factor to this.…”
Section: Discussionmentioning
confidence: 99%